2014
DOI: 10.5606/ehc.2014.04
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of proximal femoral locking plate versus 95-degree angled blade plate in the treatment of reverse intertrochanteric fractures

Abstract: The mean time to union was 17 weeks (range 14-28) and 18 weeks (range 16-32) in the PFLP group and ABP group, respectively. Implant failure and/or nonunion was observed in two patients (10%) in the PFLP group and in three patients (12%) in the ABP group. There was no statistically significant difference between the groups with regard to the Harris hip scores, time to union, need for reoperation due to mechanical problems, and complication rates (p>0.05). Conclusion: Our study results show that these two fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
(57 reference statements)
0
11
0
2
Order By: Relevance
“…Trokanterik bölge kırıkları kaynamaması %1-2 oranındadır (6,7,13). Bizim çalışmamızda kaynamama oranı %11 olarak belirlenmiştir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Trokanterik bölge kırıkları kaynamaması %1-2 oranındadır (6,7,13). Bizim çalışmamızda kaynamama oranı %11 olarak belirlenmiştir.…”
Section: Introductionunclassified
“…Azboy ve arkdaşlarının yaptığı çalışmada proksimal femoral kilitli kompresyon plağı ile tedavi edilen hastaların ortalama kaynama süresi 17 hafta, açılı plakla tedavi edilen hastaların ortalama kaynama süresi 18 hafta olarak bulunmuştur (13 Hiçbir hastamızda implant kırığı görülmedi. 48 hastanın 5 'inde kaynamama ve 2 si yüzeyel, 1 'i derin olmak üzere toplam 3 hastamızda enfeksiyon görüldü.…”
Section: Introductionunclassified
“…Information is limited on patient satisfaction with the outcome of various management methods. [1] There are studies with new fixators showing that external fixation can provide results that are similar to those obtained with conventional internal fixation techniques. [2,3] Furthermore, Moroni et al [4] concluded that surgeons should consider using the fixator with hydroxyapatitecoated pins for better fixation in the treatment of fractures in patients with osteoporosis.…”
mentioning
confidence: 99%
“…Moreover, there may be secondary trochanteric or femoral shaft fracture, peroneal nerve injury, malrotation, instability, varus deformity, malunion or nonunion [4]. Recently, to minimize the possible complications, PFLP's which possess high pullout strength and stable strength with constant angle [4]. The advantage of locking plates is that it allows achieving stable fixation at various angles and leads to less footprint compared to large proximal lag screws [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in fractures in which the fracture line is extending through trochanter major, there are some difficulties in reduction and nail placement. Moreover, there may be secondary trochanteric or femoral shaft fracture, peroneal nerve injury, malrotation, instability, varus deformity, malunion or nonunion [4]. Recently, to minimize the possible complications, PFLP's which possess high pullout strength and stable strength with constant angle [4].…”
Section: Introductionmentioning
confidence: 99%